(3GdeYJeO aj GdCOhjI GdeaQOIs - (3YeQ Hf jhSa Hf YeQ Hf Ydj Hf QShd, CHh MaU, eegO GdOjf, Gdedc GdCTQa,J (B696 (3g` s
(3ChdgG (B:s
(3hHYO (B: (3aEfi GNJUQJ gPG GdcJGH ef cJH cHGQ LeYJ GdJWhjd hGdESgGH , hde CPcQ EdG GdehLhO s
(3BNQgG (B:s
(3hgh MGQ jGHS jSgd GdHdZe , hbO JbOe PcQ GdfGaSjG ai ehVYg ef gPG GdcJGH s
(3GdeDda gh KGfi edhc GdOhdI GdQShdjI ai Gdjefs
(3gPg GdfSNI GSJYedJ GdCMHGQ GdedhfI dcJGHI CSeGA GdeaQOGJ ai GdMhGTis
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B69 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B6s
Keywords: (3GdWHs